2014
DOI: 10.5817/cp2014-1-3
|View full text |Cite
|
Sign up to set email alerts
|

Bringing sexy back: Reclaiming the body aesthetic via self-shooting

Abstract: This paper is based on visual narrative analysis of cyber-ethnographic material from a 2.5 year fieldresearch with 'not safe for work ' [NSFW] bloggers and self-shooters on tumblr.com. I use Koskela's concept of 'empowering exhibitionism ', Waskul's 'erotic looking glass', and Foucault's 'technologies of the self' to analyze self-shooting (taking photos of one-self). Constricting societal norms of sexuality, body shape and body practices influence how my participants (N=20, 10 female, 9 male, 1 transgender, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
68
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(69 citation statements)
references
References 50 publications
0
68
0
1
Order By: Relevance
“…For example, McLean et al (2015) demonstrated that adolescent girls who regularly share selfies on SNS also experienced more negative body affect (i.e., over-evaluation of shape and weight, body dissatisfaction) and increased levels of dietary restraint and internalization of the thin-ideal. In contrast, taking sexy selfies has been found to serve as a practice of accepting one's body that can increase life-satisfaction and contribute to positive body affect (Tiidenberg, 2014;Tiidenberg and Cruz, 2015). Future research designs should allow for further investigating these negative and positive associations in terms of causal relationships: It is important to consider whether body concerns arise as a consequence of engagement in selfie-behavior, or whether online self-presentation through selfies is used to regulate emotions and feelings about one's appearance and to boost one's selfesteem (cf.…”
Section: Discussionmentioning
confidence: 99%
“…For example, McLean et al (2015) demonstrated that adolescent girls who regularly share selfies on SNS also experienced more negative body affect (i.e., over-evaluation of shape and weight, body dissatisfaction) and increased levels of dietary restraint and internalization of the thin-ideal. In contrast, taking sexy selfies has been found to serve as a practice of accepting one's body that can increase life-satisfaction and contribute to positive body affect (Tiidenberg, 2014;Tiidenberg and Cruz, 2015). Future research designs should allow for further investigating these negative and positive associations in terms of causal relationships: It is important to consider whether body concerns arise as a consequence of engagement in selfie-behavior, or whether online self-presentation through selfies is used to regulate emotions and feelings about one's appearance and to boost one's selfesteem (cf.…”
Section: Discussionmentioning
confidence: 99%
“…As Katrin Tiidenberg (2014) points out in her research on NSFW self-shooting, the accepting sexual publics afforded by platforms such as Tumblr have remained separate from the shaming, negativity, and snarkiness that characterize much of social media exchange. On Tumblr, sexual selfshooting allowed rendering one's body an object of sexual desire independent of one's precise orientations (see Tiidenberg, 2016;Tiidenberg & Gómez Cruz, 2015).…”
Section: Curated Dicksmentioning
confidence: 99%
“…Katrin Tiidenberg has analysed Tumblr communities that share erotic selfies (K. Tiidenberg and Gomez Cruz 2015;Katrin Tiidenberg 2014), while Crystal Abidin has written about the "subversive frivolity" of influencers' selfies (Abidin 2016).…”
Section: Blogs and Writing About The Selfmentioning
confidence: 99%